2015
DOI: 10.1108/nbri-01-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of technological innovation on eco-efficiency of industrial enterprises in China

Abstract: Purpose – This paper aims to investigate the relation between technological innovation modes and their impact on eco-efficiency of industrial enterprises in China. Design/methodology/approach – This paper first constructs a model to evaluate and measure the eco-efficiency of industrial enterprises in China from 2006 to 2010. Second, this paper compares the role of technological innovation modes – specifically, domestic independent innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Using the super-efficiency DEA technique, they analyzed urban collection of eco-efficiency and their findings indicated that technological progress improves the growth rate of eco-efficiency. Wan et al (2015) examined the impact of technological innovation on eco-efficiency in the industrial sectors in China and their findings were that, overall, technological innovation improves environmental efficiency. Yasmeen et al (2020) also investigated the roles of technological innovation in eco-efficiency in China.…”
Section: Environmental Efficiency Using Dea Methodsmentioning
confidence: 99%
“…Using the super-efficiency DEA technique, they analyzed urban collection of eco-efficiency and their findings indicated that technological progress improves the growth rate of eco-efficiency. Wan et al (2015) examined the impact of technological innovation on eco-efficiency in the industrial sectors in China and their findings were that, overall, technological innovation improves environmental efficiency. Yasmeen et al (2020) also investigated the roles of technological innovation in eco-efficiency in China.…”
Section: Environmental Efficiency Using Dea Methodsmentioning
confidence: 99%
“…Our study is relevant to the literature regarding the effects of environmental regulations on firms’ behaviour and on social welfare, including Carraro and Soubeyran (1996), Amacher and Malik (2002), Fischer et al (2003), Drake et al (2010), Krass et al (2013), Atasu et al (2013), Lao (2014) and Wan et al (2015), etc. For instance, Carraro and Soubeyran (1996) assumed that a firm possesses both “dirty” and “clean” technologies and found that emission taxes induce firms to clean production technology, which reduces output, raises prices and hampers consumers’ surplus.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the theory of social interaction, existing studies have suggested that to avoid the negative results of uneconomical costs and uncertain outcomes caused by resource and capacity constraints, firms imitate their peers in the same social network or those with similar characteristics in the process of making and implementing decisions, thereby highlighting peer effects (Manski, 1993, 2000). For example, Wang and Chu (2022) studied Chinese listed manufacturing firms and found that firms closely follow their peers' green innovation within the same industry, which also highlights green innovation peer effects. Additionally, Tan et al (2022) regarded firms in upstream and downstream industries as peers and found that peer firms influence the quality of green innovation.…”
Section: Introductionmentioning
confidence: 99%